Change in WHO cardiovascular risk prediction over three years in PLWH on efavirenz-based ART - Melani Ratih Mahanani; Ethel Rambiki; Tapiwa Kumwenda; Claudia Wallrauch; Tom Heller; Volker Winkler; Florian Neuhann; Hans-Michael Steffen (Southern African Journal of HIV Medicine, 2025)
No abstract available.